GENDER STEREOTYPES IN INDONESIAN PUBLIC COMPANIES’ PERFORMANCE - Rahayu, Sri Mangesti; Ramadhanti, Wita; Rahayu, Dyah Sulistyowati; Osada, Hiroshi; Indrayanto, Adi (Universitas Brawijaya, Indonesia, 2019)
Gender equality is one important item from the United Nation’s Sustainable Development Goals (SDGs). It makes a gender gap in companies’ top management becomes valuable to be studied because people still have a stereotype that leadership is a masculine job. This research will test the effect of performance, payment, bankruptcy risk, and earnings management. Data is taken from Indonesian public companies in 2016 using means different statistical test. The result shows that 30.9% or minority corporation have a female director. Hence, while women were given the opportunity to lead, the companies will have better performance and compensation than their male only board of director counterparts. It is proof that gender stereotypes happen in Indonesian Public Companies Leadership.